Living Art Indonesian Artists Engage Politics, Society and History. - Kent, Elly; Hooker, Virginia; Turner, Caroline, 1947- (Asian studies series., 2022)
Living Art: Indonesian Artists Engage Politics, Society and History is inspired by the conviction of so many of Indonesia’s Independence-era artists that there is continuing interaction between art and everyday life. In the 1970s, Sanento Yuliman, Indonesia’s foremost art historian of the late twentieth century, further developed that concept stating: ‘New Indonesian Art cannot wholly be understood without locating it in the context of the larger framework of Indonesian society and culture’ and the ‘whole force of history’. The essays in this book accept Yuliman’s challenge to analyse the intellectual, socio-political and historical landscape that Indonesia’s artists inhabited from the 1930s into the first decades of the new millennium, including their responses to the COVID-19 pandemic.